Continuous glucose monitoring in subjects undergoing bariatric surgery: Diurnal and nocturnal glycemic patterns - Lupoli, Roberta; Lembo, Erminia; Ciciola, Paola; Schiavo, Luigi; Pilone, Vincenzo; Capaldo, Brunella (Nutrition, metabolism, and cardiovascular diseases, 2020)
Although the use of Continuous Glucose Monitoring (CGM) is rapidly extending, little evidence is currently available on daily glycemic excursions after different bariatric procedures. We assessed glycemic patterns after sleeve gastrectomy (SG) and roux-en-Y gastric bypass (RYGB) using CGM. Cross-sectional study in subjects who had undergone RYGB (n = 22) or SG (n = 29) since at least 1 year, without pre-surgery or in current diabetes (T2DM) remission. All subjects underwent 7 day-CGM (Dexcom G4 PLATINUM), which provides glucose variability (GV), number and time spent in hypoglycemia, hypoglycemia patterns (postprandial, nocturnal or mixed). All indexes of GV were higher after RYGB than after SG (p < 0.001). Twenty-eight (55%) subjects experienced hypoglycemia. The number of events was higher after RYGB than SG (p = 0.017) while it did not differ in subjects with or without pre-surgery T2DM (p = 0.129). Overall, 9 (32%) subjects presented hypoglycemia exclusively during the postprandial period, 8 (29%) an exclusively nocturnal pattern and 11 (39%) a mixed pattern. The nocturnal pattern was more frequent after SG than RYGB (53.8% vs 6.7%, p = 0.036) while no difference was observed in subjects with or without pre-surgery T2DM (p = 0.697). Hypoglycemia symptoms were more frequent in subjects with postprandial than in those with nocturnal pattern (77.8% vs 12.5%, p = 0.015). RYGB is characterized by a greater GV and a higher number of hypoglycemia events mostly post-prandial and symptomatic, while SG is associated with nocturnal and often asymptomatic hypoglycemia. These findings suggest that post-bariatric hypoglycemia is a more complex, not exclusively, postprandial phenomenon. •Continuous glucose monitoring is an useful tool to detect both symptomatic and asymptomatic hypoglycemia in bariatric patients.•Post-bariatric glycemic patterns present distinct characteristics according to the type of surgical procedure.•Roux-en-Y gastric bypass is characterized by a greater glucose variability and a more severe hypoglycemia than sleeve gastrectomy.•Hypoglycema is mainly postprandial after roux-en-Y gastric bypass and prevalently meal-independent after sleeve gastrectomy.•Post-bariatric hypoglycemia should no longer be considered an exclusively postprandial phenomenon.